COMPULSORY EDUCATION DAN SISTEM PEMBIAYAAN PENDIDIKAN SERTA KONSEP PENDIDIKAN GRATIS DALAM ISLAM - Muhammad Ruslan (STIT Al-Ittihadiyah Labuhanbatu Utara, 2021)
This article discusses compulsory education and education financing systems in Indonesia. The discussion uses manuscript studies. The compulsory education concept approach describes the basis of laws that regulate the right to universal education. One of the laws that govern this problem is the National Education System Law No. 20 of 2003 that,